Pkd2 Affects Cilia Length and Impacts LR Flow Dynamics and Dand5 - Jacinto, Raquel (2021)
Funding: This work was supported by the Fundação para a Ciência e a Tecnologia (FCT-ANR/BEX-BID/0153/2012 research grant). SL is funded by an FCT CEEC contract for Principal Investigator. The work was also supported by Sociedade Portuguesa de Nefrologia (research grant 2015), iNOVA4Health – UID/Multi/04462/2013 (a program financially supported by Fundação para a Ciência e Tecnologia/ Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement) and Fundação para a Ciência e Tecnologia (research grant – PTDC/BEXBID/1411/2014). MR-R was supported by national funds through Fundação para a Ciência e Tecnologia, in the context of the celebration of the program contract foreseen in the numbers 4, 5, and 6 of article 23 of D.L. no. 57/2016 of 29 August, as amended by Law no. 57/2017 of 19 July. Zebrafish used as animal model were reared and maintained in the CEDOC Fish Facility, with the support from the research consortia Congento, co-financed by Lisboa Regional Operational Program (Lisboa2020), under the Portugal 2020 Partnership Agreement, through the European Regional Development Fund (ERDF) and Fundação para a Ciência e Tecnologia